Recent Advancements in Planning and Reliability Aspects of Large-Scale Deep Sea Offshore Wind Power Plants: A Review - Pawan Kumar; Santanu Paul; Akshay Kumar Saha; Omkar Yadav (IEEE Access)
The transition towards renewable energy sources has propelled the rapid expansion of offshore wind power, with large-scale deep offshore wind power plants (OWPPs) emerging as a promising solution to meet escalating energy demands while mitigating climate change. This comprehensive review delves into recent advancements in the planning and reliability aspects of large-scale deep offshore wind power plants, crucial determinants of project success, economic viability, and long-term sustainability. The review synthesizes current research findings, technological innovations, and industry practices, and the evaluation elucidates state-of-the-art methodologies, tools, and strategies employed in developing and operating these offshore renewable energy assets. Key focus areas include site selection and resource assessment, technological innovations in turbine design and foundation systems, risk assessment and mitigation strategies, grid integration, and socio-economic and environmental considerations. The review identifies emerging trends, future research directions, and policy implications by critically analyzing these dimensions, offering valuable insights for researchers, practitioners, policymakers, and investors engaged in global sustainable offshore wind energy deployment.